A pilot trauma registry in Peshawar, Pakistan – A roadmap to decreasing the burden of injury – Quality improvement study. (December 2021) - Tanoli, Omaid; Ahmad, Hamza; Khan, Haider; Khattak, Farhad Ali; Khan, Awais; Mikhail, Alexandre; Deckelbaum, Dan; Razek, Tarek
Abstract: Background/local problem: In Pakistan, trauma is a significant public health issue accounting for the second leading cause of disability and fifth for healthy years of life lost. Well-developed trauma systems, utilizing trauma registries, have been proven to decrease morbidity and mortality from injuries, and helped to reduce the number of injured patients. In Pakistan, most data on injury are acquired through methods that are retrospective, incomplete, and open to recall bias. To that end, a trauma registry was piloted at the Lady Reading Hospital (LRH) in Peshawar, Pakistan to elucidate the importance of trauma registries in designing healthcare targeted quality improvement initiatives. Intervention: Upon receiving ethics approval, a twenty-five-point registry was piloted at the Lady Reading Hospital. Methods: The pilot implementation was carried out from May 9th to May 13th, 2018. Results: A total of 267 patients were included in the pilot registry. Motor vehicle collisions were the most prevalent cause of injury (46%). The other causes of injury included falls (24%), blunt assaults (9%), stabs/cuts (8%), gunshots (6%), crush injuries (3%), burns (2%), and blasts/landmines (2%). Most patients were treated in the trauma bay and required no further acute intervention (51%). Conclusion: This 5-day pilot trauma registry was the first of its kind in Peshawar, Pakistan, and despite its short course, an immense amount of data was garnered on the epidemiology of injury in the region. Significantly, the data collected can already be used to develop evidence-based changes, which will effectively minimize the impact of trauma. Highlights: 267 patients were captured over the course of 5 days. Motor vehicle accidents were the most prevalent cause of injury. Private ambulances were the most common form of transportation. Registry accurately described the epidemiology of injury in the region. Study displays the feasibility of a long-term registry in Northwestern Pakistan.